Targets on superhydrophobic surfaces for laser ablation ion sources - Renisch, Dennis; Beyer, Thomas; Blaum, Klaus; Eibach, Martin Andreas; Smorra, Christian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2012)
Target preparation techniques for a laser ablation ion source at the Penning-trap mass spectrometer TRIGA-TRAP have been investigated with regard to future experiments with actinides. To be able to perform mass measurements on these nuclides considering their limited availability, an efficient target preparation technique is mandatory. Here, we report on a new approach for target production using backings, which are pretreated in a way that a superhydrophobic surface is formed. This resulted in improved targets with a more homogeneous distribution of the target material compared to standard techniques with unmodified backings. It was demonstrated that the use of these new targets in a laser ablation ion source improved the ion production significantly.
Gesehen am 18.05.2018